Journal Economics, business & accountancy: SMALL, MEDIUM, MICRO ENTERPRISES, AND FINANCIAL GROWTH CYCLE - Elok Pakaryaningsih (PPPM Perbanas, 2011)
Research on small, medium, and micro-sized enterprises (SMMEs) is considered interesting.This study attempts to examine the existence of external financing on micro, small and mediumenterprises in Jogjakarta, especially to support the existence of The Financial GrowthCycle Model proposed by Bergel and Udell (1998